Luminescent platinum(II) complexes with functionalized N-heterocyclic carbene or diphosphine selectively probe mismatched and abasic DNA - Sin Ki Fung (Nature Portfolio, 2016)
DNA pairing defects such as mismatched and abasic DNA are prevalent in cancer cells. Here, the authors present luminescent platinum based probes capable of preferentially binding to mismatched and abasic DNA, and reporting this by a significant luminescence enhancement